2014
DOI: 10.1097/wnf.0000000000000010
|View full text |Cite
|
Sign up to set email alerts
|

Long-term Safety of Rivastigmine in Parkinson Disease Dementia

Abstract: This study supports the long-term safety of rivastigmine in Parkinson disease dementia. The rate of worsening of motor symptoms was in the range expected due to the natural progression of Parkinson disease, no new or unexpected safety issues emerged in the long-term.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 66 publications
(41 citation statements)
references
References 8 publications
(11 reference statements)
0
36
0
2
Order By: Relevance
“…The long-term safety data from a 76-week, prospective, open-label, randomized study97 in patients with mild-to-moderate PDD (n=583) showed that treatment with rivastigmine capsule (12 mg/day) or patch (9.5 mg/24 h patch) was well tolerated. The commonest adverse events (AEs) with rivastigmine capsules and patch were nausea (40.5% and 8.3%, respectively), tremor (24.5% and 9.7%, respectively), fall (17.0% and 20.1%, respectively), vomiting (15.3% and 2.8%, respectively), and application site erythema (0% and 13.9%, respectively).…”
Section: Rivastigmine In Pddmentioning
confidence: 99%
“…The long-term safety data from a 76-week, prospective, open-label, randomized study97 in patients with mild-to-moderate PDD (n=583) showed that treatment with rivastigmine capsule (12 mg/day) or patch (9.5 mg/24 h patch) was well tolerated. The commonest adverse events (AEs) with rivastigmine capsules and patch were nausea (40.5% and 8.3%, respectively), tremor (24.5% and 9.7%, respectively), fall (17.0% and 20.1%, respectively), vomiting (15.3% and 2.8%, respectively), and application site erythema (0% and 13.9%, respectively).…”
Section: Rivastigmine In Pddmentioning
confidence: 99%
“…Based on this study rivastigmine became the fi rst specifi c treatment approved for the treatment of patients with mild to moderate PD-D. A patch form of rivastigmine also became available and has been approved for PD-D in several countries. Its long-term efficacy and safety as compared to capsules has been described in a large open-label prospective study, revealing no long-term safety concerns, in particular with regard to worsening of motor symptoms [ 103 ].…”
Section: Cholinesterase Inhibitorsmentioning
confidence: 99%
“…Adeno-associated virus gene therapy I/II [113] CERE-120 (AAV2-Neurturin) Adeno-associated virus gene therapy Trophic II Target: Putamen + SN [114] NLX-P101 Adeno-associated virus gene therapy encoding glutamic acid decarboxylase II [115] Ion channel blockers other than the NMDA receptor, other receptor antagonists NGP1-01 [120] Pimavanserin Inverse agonist on the serotonin 5-HT [125] Other enzyme inhibitors Rivastigmine Butyrylcholinesterase and acetylcholinesterase inhibitor IU Early--to-late PD Cognitive and functional decline associated with PD with dementia [127] AZD-3241 (structure not yet disclosed)…”
Section: Comt Inhibitors Tolcaponementioning
confidence: 99%
“…Rivastigmine (Table 1) [127] is a dual cholinesterase inhibitor, and is active on both acetylcholinesterase and butyrylcholinesterase, and both enzymes constitute valid drug targets for PD. A large randomized placebo-controlled trial demonstrated that oral rivastigmine in 541 patients improved attention and executive functions, activities of daily living, behavioral symptoms and cognition after 6 months of treatment.…”
Section: Other Enzyme Inhibitorsmentioning
confidence: 99%